Access to innovative cancer medicines in a middle-income country - the case of Mexico - Daniela Moye-Holz; Rene Soria Saucedo; Jitse P van Dijk; Sijmen A Reijneveld; Hans V Hogerzeil (Taylor & Francis Group, 2018)
Background Cancer has become the third cause of death in Mexico. Treatment for cancer is often complex and lengthy. New and better medicines enter the market at high prices, which may limit access. Like most Latin American countries, Mexico has an essential cancer medicines list that includes innovative medicines. Their accessibility and use in the public sector remains unknown. Therefore, we describe the use, as a proxy of access, of innovative and essential cancer medicines in the public sector in Mexico, by insurance institution, and by five regions between 2010 to 2016. Methods We used drug utilization research methods to assess the use of eight patented cancer medicines. Through the national transparency platform, we obtained data on the quantities of these medicines used in all public health facilities and social health insurance institutions and recalculated those figures into defined daily dose (DDD) per 1000 population per year. Results Overall, the use of all medicines increased over the years, especially for trastuzumab, rituximab and imatinib. The use of innovative medicines was higher per population covered in social health insurance institutions than in governmental facilities. Throughout the study period, the Central region (including Mexico City) has used more medicines per population than the other regions. Conclusions The use and access of some essential innovative cancer medicines has increased over the years, but remains unequal across insurance schemes and regions. Particularly, the Ministry of Health Insurance scheme and Northern and Western regions in the country would benefit from additional efforts to increase access to essential cancer medicines.